Urinary cysteinyl progestogens: Occurrence and origin. Issue 152 (August 2015) - Marcos, Josep; Pol, Marta; Fabregat, Andreu; Ventura, Rosa; Renau, Nuria; Hanzu, Felicia A.; Casals, Gregori; Marfà, Santi; Barceló, Bernardí; Barceló, Antonia; Robles, Juan; Segura, Jordi; et al.
Graphical abstract: Highlights: 16-Cysteinyl-progesterone and 16-cysteinyl-pregnenolone are excreted in human urine. Chemically synthesized materials and LC–MS/MS allowed unequivocal identification. Different experiments point toward an adrenal origin for both novel progestogens. 16-Cysteinyl-progesterone is also produced by the ovaries but not by the placenta. Human hepatocytes do not convert progesterone to 16-dehydroprogesterone. Abstract: The presence of two cysteinyl progestogens, 16-cysteinyl-progesterone (16-Cys-Prog) and 16-cysteinyl-pregnenolone (16-Cys-Preg), in human urine is described for the first time. Their occurrence was unequivocally confirmed by comparison with synthesized material by using mass spectrometric detectors. Several experiments were performed in order to clarify their origin. The adrenal origin of both 16-Cys-Prog and 16-Cys-Preg can be inferred from the increase in their concentrations after ACTH stimulatory test, together with their circadian variation similar to the one observed for cortisol. Moreover, the notable increase in excretions of 16-Cys-Prog during the luteal phase of the menstrual cycle points towards an ovarian production for this progestogen. However, the analysis of samples during the course of two pregnancies revealed that, in spite of the large amounts of progesterone produced during gestation, the human placenta lacks the capacity to make 16-Cys-Prog. The adrenal and ovarian origin has been further indicated by the absence of both metabolites in samples collected from a subject with bilateral adrenalectomy and hypogonadotrophyic hypogonadism. Regarding liver action, in vitro studies with hepatocytes and progesterone indicate that, although the liver is able to metabolize progesterone to 6-dehydroprogesterone, it has not the enzymatic machinery for the generation of 16-dehydroprogesterone. Taken together, these results open the possibility for a noninvasive test for the simultaneous evaluation of progesterone biosynthesis in different organs.